ASPECTS OF SURGERY OF ABDOMINAL HERNIATION AND COMBINED PATHOLOGY OF ABDOMINAL ORGANS - Sherbekov Ulugbek Akhrarovich; Makhmudov Timur Bahadirovich (Scholar Express Journals, 2023)
The study included the results of treatment of 331 patients with ventral hernia and concomitant pathology of the abdominal organs. Simultaneous pathology of the abdominal organs, requiring surgical correction for ventral hernias, was 52.8%. Most often, such diseases as: cholelithiasis (30.1%), pathology of the pelvic organs in women (30.8%), adhesive disease of the abdominal cavity and chronic intestinal obstruction (46.7%), as well as obesity III - IV degrees and abdominoptosis (29.7%). When concomitant abdominal pathology is located at a remote distance from the hernial defect (M1S8 or M3S2), the priority is to perform a simultaneous stage using laparoscopic technique, which was successfully performed in 37.5% of patients, that is more than 1/3 of patients of the main group. Optimization of the tactical and technical aspects of the one-time surgical correction of ventral hernias and combined abdominal pathology with the priority use of endovideosurgical technologies and tensionfree alloplasty methods made it possible to reduce the incidence of postoperative complications from 8.6% to 5.3%, to reduce the duration of the operation from 72.5 ± 3.4 min. up to 58.5±4.1 min. and reduce the duration of inpatient treatment from 10.2±0.4 to 8.3±0.6 bed days.
Keywords: abdominal hernia; simultaneous operations